The implications of the coronavirus pandemic on some educational systems – A systematic review of educational researches – - Albakr, Fawziah Bakr Rashid; Altamimi, Fatima Abdulrahman Abdulla; Alsalem, Huda Salem Hamed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the statues of education in times of emergency and crises, during the Corona pandemic in particular. According to what was covered by the studies included in this review, to draw out the most important issues that the studies addressed during the Corona pandemic, and to know the most common and most effective educational practices during the Corona pandemic crisis as reviewed by these studies. The researchers used the systematic review method, which is one of the types of literature review that uses systematic methods to collect secondary data, evaluate the studies selected for the review critically, and then collect the results from a quantitative and qualitative point of view. The research sample included 22 Arabic and English studies related to the topic of education at the time of emergencies and crises, especially during the crisis of the Corona pandemic. The study reached the following results: the importance of continuing education after the Corona pandemic by adopting e-learning education systems and also the social media, immediate activation of all educational platforms provided by education systems at the time of the pandemic, and the importance of developing an integrated strategy for virtual distance education, and making administrative services available online Including registration, acceptance and outcomes, and designing programs and websites that ensure the continuation of e-learning even after the end of the pandemic. The results of this study also showed a number of challenges that faced education systems during the Corona pandemic. The most important of which is the poor preparation of teachers and students in the skills needed to use e-learning programs, use of modern technology, and enhance their abilities to deal with programs and platforms prepared for education and electronic evaluation, and the lack of electronic means and devices is one of the most important challenges. The results of this study revealed psychological difficulties (stress, anxiety, depression and many fears among the learners) that were left by distance education during the Corona pandemic, and the psychological impact of learners contributed to a decrease in their motivation towards learning. The study calls for the inclusion of e-learning (distance) within the framework of work policies in global education systems as a simultaneous education system with urban education, preparing and training students, teachers and faculty members on the skills necessary to use e-learning programs with high efficiency.
Keywords: The implications of the coronavirus pandemic; educational systems; a systematic review